ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA DENGAN HIRADC (STUDI KASUS : PEMBANGUNAN/REHABILITASI GEDUNG KEJAKSAAN TINGGI PROVINSI KALIMANTAN TENGAH) - Priambudi, Januar Amin; Puspasari, Veronika Happy; Nuswantoro, Waluyo; Purwantoro, Almuntofa (Jurnal Civil Engineering Study, 2023)
Risk is the combination of the likelihood of a hazardous event or exposure with the severity of injury or impairment to health caused by the event or exposure. Every activity carries a risk of success or failure. The purpose of this study is to identify the construction and determine the assessment for each work item. The results of the hazard identification process that can occur include dehydration / heat exhaustion; back pain; inhalation of dust / cement; errors in lifting, shifting, and moving; inhalation of paint and thinner odors; exposed to sharp objects. By combining opportunities and consequences, the work items with the highest risk of hazards are mechanical electrical plumbing with 24 risks, the second highest risks are structural and architectural work with 14 risks each, and the lowest risk level is in preparation work with 3 risks.